Pathways relevant to Alzheimer's disease are identified during proinflammatory activation from a microglial model derived from human monocytes. (1st February 2022) - Chen, Jingchun; Banerjee, Atoshi; Petereit, Juli
Abstract: Background: Microglia are the primary immune cells of the central nervous system. These immune cells play a crucial role in maintaining the brain homeostasis. Neuroinflammation, usually mediated by microglial activation, is a common feature of many neurodegenerative disorders, such as Alzheimer's disease (AD). Understanding the microglial proteome during their activation will provide insights into the mechanisms of how genes and pathways maintain brain homeostasis or contribute to disease progression. Method: In this study, we first generated the in vitro microglia‐like cells (iMGCs) that were induced from peripheral monocytes of three individuals. We then activated the iMGCs into an M1 (pro‐inflammatory) state with lipopolysaccharide (LPS) treatment. We then conducted comprehensive proteomics analysis to determine gene and pathway regulations during the LPS‐treated M1 microglial activation via data‐independent acquisition mass spectrometry. Result: Not surprisingly, we found that the LPS‐treated microglia upregulated genes were enriched in cytokine‐cytokine receptor interaction or chemokine signaling pathway (IL‐1β, IL‐6, CXCL family), TNF‐α signaling pathway (TRAF1, TNFAIP6, PTGS2), or NF‐ƙB (NF‐ƙB2) pathway. We also found that TNF‐α, NF‐ƙB1, RELA, and IL‐1β were likely to function as the upstream regulators during the microglial activation. More interestingly, our data indicated that M1 microglia activation underwent significant changes in biological processes, including neuroinflammatory response, regulation of signaling receptor activity, and glial cell activation. Conclusion: Therefore, our study indicated that a human monocyte‐derived microglia model treated with a pro‐inflammatory agent such as LPS could provide microglia‐specific regulations during M1 activation and further identify disease‐relevant genes, biological processes, or pathways. The study implements that the microglial model can be used in clinical studies for new biomarker or drug discovery for many neuroinflammatory disorders, including AD. Further studies with this microglial model in AD patients are warranty to verify our finding.